Effect of Dietary Inclusion of Chitosan on Survival and Selected Cellular Antioxidants in Drosophila melanogaster - O.G. Igharo; L.I. Abadaike; J.O. Osunbor; I.C. Owie; A.I. Aruomaren; E.L. Igharo; K.I. Ikeke (Journal of Applied Sciences and Environmental Management)
This study evaluated the effect of dietary inclusions of different concentrations of chitosan on survival rate and some oxidative stress markers in Drosophila melanogaster (Harwich strain). Flies were raised on diet supplemented with chitosan for 7 days and 14 days for survival assay. The survival assay was used to evaluate their survival rate. The flies were subsequently homogenized and the oxidative stress markers gluthathione, gluthathione-Stransferase and catalase were assayed. As observed, Drosophila flies fed with 10μg, 20μg, 40μg, 320μg, 640μg, 1mg chitosan meal had a higher survival rate compared to control. 320μg of chitosan meal had the highest survival rate (96%), indicating that the Drosophila flies was more tolerable to this concentration. It was observed that inclusions of chitosan in their meal especially at 320μg concentration increased their survival rate compared to control. Activities of gluthathione, catalase were increased in flies fed with diet supplemented with chitosan than in control. These results have shown that dietary inclusions of chitosan in various concentrations increased the survival rate of the flies than in control which contained only water and also increase some antioxidant enzymes in the flies than in control. Reduced antioxidant levels have been linked to accelerated aging and conditions leading to death like cancer. Based on the fact that antioxidant slow aging process and reduces risks of life threatening conditions. The result indicated that chitosan inclusion in Drosophila meals may modulate oxidative stress status in Drosophila melanogaster and increase survival rate.